Correction: Design of foldable, responsively drug-eluting polyacrylic intraocular lens bulk materials for prevention of postoperative complications. Issue 43 (1st November 2022) - Hong, Yueze; Zou, Haoyu; Hu, Yulin; Fei, Fan; Liang, Lin; Liu, Dong; Han, Yuemei; Lin, Quankui
Abstract : Correction for 'Design of foldable, responsively drug-eluting polyacrylic intraocular lens bulk materials for prevention of postoperative complications' by Yueze Hong et al., J. Mater. Chem. B, 2022, DOI: ; https://doi.org/10.1039/d2tb01974d .